Development of Wind Operated Passive Evaporative Cooling Structures for Storage of Tomatoes - Sunmonu, M. O.; Chukwu, Ogbonnaya; Haff, Ron (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2016)
A Wind operated passive evaporative cooler was developed. Two cooling chambers were made with clay container (cylindrical and square shapes). These two containers were separately inserted inside bigger clay pot inter- spaced with clay soil of 7 cm (to form pot-in-pot and wall-in wall) with the outside structure wrapped with jute sack. The soil and the jute sacks were wetted with salt solution. Five blades were constructed inside the cooling chambers with aluminium material which were connected with a shaft to a vane located on a wooden cover outside the cooling chamber. The vanes (made of aluminium) were to be powered by the wind which in turn rotates the blades inside the cooling chamber. The total volume of 40500cm3 and storage capacity of 31500cm3 were recorded for the square structures while total volume of 31792.5cm3 and storage capacity of 24727.5cm3 were recorded for the cylindrical structures. During the test period, the average temperatures of 27.07oC, 27.09oC and 33.6oC were obtained for the pot-in-pot (cylindrical), wall-in-wall (square) and the ambient respectively. The average relative humidity of 92.27%, 91.99% and 69.41% were obtained for the pot-in-pot (cylindrical), wall-in-wall (square) and the ambient respectively. The average minimum and maximum wind speed recorded for the month of October was 2.5m/s and 2.6m/s respectively.